Time-limited leases in radio systems. - Chapin, John M. (IEEE Communications magazine)
A time-limited lease is a set of rights that expires after a specified duration. We analyze ways to use leases to facilitate innovation in radio devices and wireless communication. In our vision, manufacturers include in their devices a simple, secure subsystem that contains a clock and disables specific transmit capabilities if no extension message is received by the end of the lease period. When devices provide this support, regulators may use certification leases rather than permanent grants to accelerate deployment of innovative radios. Spectrum rights holders may use leases to reduce risk in secondary spectrum market transactions. Firms collaborating in innovative wireless service business models can better retain control of their respective rights. We examine both the technical and policy issues associated with leases.